PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI SAINS (MOSA Game) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI PERPINDAHAN KALOR KELAS V MIN 1 JOMBANG - Fajriyah, Syifaul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ABSTRACT This research is motivated by the lack of learning media at MIN 1 Jombang. This resulted in a decrease in students' understanding of concepts, especially in science subjects. This research and development purpose to (1) develop Monopoly Science learning media (MOSA Game) on heat transfer material, (2) examine the feasibility of the product to find out an increase in understanding the concept of heat transfer material, and (3) find out student responses regarding the attractiveness of the Monopoly Science learning media. This type of research is Research and Development (R&D). The model in this research and development is the model of Prof. Sugiyono. The results of the validation of learning media by three validators with an average percentage of 87%. With design validation 90.26%, content validation 85.56%, language validation 83.33%. This learning media is effective in increasing the understanding of concepts, it is based on the results of the pretest-posttest students who were tested for N-Gain with an average value of 0.65 in the